Recombinant human erythropoietin treatment protects the cardio-renal axis in a model of moderate chronic renal failure - Teixeira, Ana Margarida (2011)
Chronic kidney disease (CKD) patients develop anemia because of the low kidney erythropoietin (EPO) production, thus promoting cardiovascular complications. The degree of renal insufficiency might determine the moment to start recombinant human erythropoietin (rhEPO) therapy, but the molecular basis for these options deserves better elucidation. This study aimed to clarify the cardio-renal effects of earlier rhEPO ther- 20 apy in rats with moderate chronic renal failure (CRF). Four groups of rats were evaluated for 15 weeks (control; rhEPO - 50 Ill/kg/week; CRF - 3/4 nephrectomy; CRF + rhEPO) to assess renal and hematology data, EPO levels, blood pressure, heart rate, peripheral catecholamines contents, serum-transforming growth factor-31 (TGF-f11), kidney gene expression of EPO, Caspase 9 (Casp9), and vascular endothelial growth factor (Vegf). This model of moderate CRF showed moderate and corrected anemia, hypertension, tachycardia, sympa- 25 thetic overactivity, and increased serum TGF-31 content. The remnant kidney showed a proliferative profile, with hypertrophy, downregulated gene expression of EPO, and upregulated gene expression of Vegf and Casp9. rhEPO treatment promoted erythrocytosis and prevented tachycardia and catecholamines increment, with a rise of serum TGF-$1. Furthermore, the decreased kidney gene expression of EPO and the overexpression of Casp9 were prevented, demonstrating a renoprotective action on the remnant kidney. In conclusion, 30 rhEPO therapy promotes a protective effect on the cardio-renal axis, which might be mainly attributed to its pro-proliferative and anti-apoptotic properties. These findings might recommend its use in earlier stages of CRF, acting as an erythropoiesis stimulating agent, to efficiently correct not only the anemia, one of the major complications in these patients, but also the succeeding adverse cardio-renal effects.